Unmet Health Needs of Roma Women in the Two Biggest Roma Communities in the Republic of Srpska, Bosnia and Herzegovina - Stojisavljevic, Stela; Grabez, Milkica; Stojanovski, Kristefer (Frontiers in Public Health, 2020)
The aim of this study was to explore the health status and the health needs of Roma women in the two biggest Roma communities in the Republic of Srpska, Bosnia & Herzegovina. Data presented in this work were collected through health assessment of 183 adult Roma women, which was the part of the Roma health improvement program. Logistic regression was used to assess the degree to which absence of medical supervision by a provider was related to the sociodemographic characteristics of Roma women. The majority of Roma women had no schooling, 62.8 % and 88.5% were unemployed, while 93.9% had a health insurance, a health card, and were registered with a Family Medicine Doctor. More than half of Roma women (60.1%) had reported chronic diseases. Majority, 68.2% reported that their chronic disease was not medically supervised. Of which, 33.64% of women cited lack of money for medical check-ups and 34.5% cited lack of money for prescribed medications. Roma women with chronic diseases were more likely to not have health insurance (P=0.003) and their disease was not under medical control (P<0.001). The results confirm that women of younger age, unmarried with primary or secondary education are more likely to be under medical supervision. Roma women in Bijeljina and Prijedor face barriers to health access and have unmet health needs due to their social and living circumstances despite the fact that universal health access is legally guaranteed to all citizens of the Republic of Srpska.